2018
DOI: 10.1073/pnas.1802902115
|View full text |Cite
|
Sign up to set email alerts
|

PRDM1 silences stem cell-related genes and inhibits proliferation of human colon tumor organoids

Abstract: PRDM1 is a tumor suppressor that plays an important role in B and T cell lymphomas. Our previous studies demonstrated that PRDM1β is a p53-response gene in human colorectal cancer cells. However, the function of PRDM1β in colorectal cancer cells and colon tumor organoids is not clear. Here we show that PRDM1β is a p53-response gene in human colon organoids and that low PRDM1 expression predicts poor survival in colon cancer patients. We engineered PRDM1 knockouts and overexpression clones in RKO cells and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…Several studies have identified an embryonic stem cell-like geneexpression signature in breast cancer (34) and in poorly differentiated aggressive human tumors (35), and such stem-like signatures usually correlate with poor prognosis. Our previous study proved that repressing stemness by epigenetic means can inhibit colorectal tumor organoid proliferation in a 3D culture system (21). We have also investigated p53 dependency of drug sensitivity in human colorectal cancer cell lines with and without TP53 deletions, and found that most of drugs have similar response patterns to what we report here in human embryonic stem cells ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Several studies have identified an embryonic stem cell-like geneexpression signature in breast cancer (34) and in poorly differentiated aggressive human tumors (35), and such stem-like signatures usually correlate with poor prognosis. Our previous study proved that repressing stemness by epigenetic means can inhibit colorectal tumor organoid proliferation in a 3D culture system (21). We have also investigated p53 dependency of drug sensitivity in human colorectal cancer cell lines with and without TP53 deletions, and found that most of drugs have similar response patterns to what we report here in human embryonic stem cells ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 74%
“…TP53 knockout hESCs and RKO cells were generated using CRISPR/Cas9 as described previously (21) with minor modifications. Briefly, human codon-optimized Streptococcus pyogenes wild-type Cas9 (Cas9-2A-GFP) was obtained from Addgene (#44719).…”
Section: Tp53 Knockout In Human Embryonic Cells and Rko Cells With Crmentioning
confidence: 99%
See 1 more Smart Citation
“…TP53 knockout MCF-7 cells were generated as previously published 45 . Human codonoptimized Streptococcus pyogenes wild type Cas9 (Cas9-2A-GFP) was obtained from Addgene (Cambridge, MA).…”
Section: Tp53 Knockout In Mcf-7 Cellsmentioning
confidence: 99%
“…As for other members of the PRDM family, the existence of an alternative protein product of the PRDM1 gene was previously described in myeloma cell lines; this protein, named PRDM1β, is generated by alternative transcription initiation using an internal promoter and it has a disrupted PR domain and lacks the amino-terminal 101 aa of the originally described protein [41]. Noteworthy, a recent study showed that PRDM1β was a p53-response gene in human colon organoids and low PRDM1 expression could predict poor survival in colon cancer patients [42]. However, today the functional role of these protein isoforms still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%